Assessment on effect of Mangifera sp. microwave extraction against bacterial activity - Afnani, Alwi@Ali; Norfazila, Saufi; Siti Rohaiza, Ruslan (2021)
Mangifera sp belongs to the family Anacardiaceae can easily be found all over tropical regions in this world, cheaper and less side effects compare to the standard drug antibiotics. In addition, Mangifera sp. have been reports as medicinal plant that possessed antibacterial activity against human pathogens. In this study, the effect of Mangifera sp leaves microwave extraction of were investigated. Standard methods were used in determine the Minimum Inhibition Concentration (MIC) using disc-diffusion agar and 96 well plate against various bacteria namely Klebsiella pneumoniae, Enterococcus faecalis, Proteus mirabilis, Salmonella enterica, Pseudomonas aeruginosa and Acinetobacter baumannii. Effect of microwave extraction of sample Mangifera was observed using few timelines such as soxhlet, 2 min, 5 min, 8 min, 10 min and 12 min. The result obtained showed that 10 min sample (M10) was the optimum time and have highest antibacterial effect compare to others timelines. M10 was used to against Acinetobacter baumannii and showed great outcome since it has zone of inhibitions of 20 mm (200 mg/ml) and MIC of 6.125 mg/ml. In summary, Mangifera sp. exhibited significant antimicrobial activity comparable to gentamycin as positive control and optimum microwave time for sample Mangifera sp is 10 min.